Amorphous Aluminosilicate Nanosheets as Universal Precursors for the Synthesis of Diverse Zeolite Nanosheets for Polymer‐Cracking Reactions. (17th October 2022) - Sasaki, Koki; Gaitan, Jose A. Hernandez; Okue, Tsuyoshi; Matoba, Shotaro; Tokuda, Yuki; Miyake, Koji; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract: Zeolites catalyze some reactions in their molecular‐sized pores, but large molecules can react only on their external surface. Zeolite‐nanosheets (NSs) have been developed as catalysts for large molecules. The previously reported methods to synthesize zeolite‐NSs are specialized for each zeolite type. Here we propose a new method to synthesize various zeolite‐NSs from the same amorphous aluminosilicate NSs (AAS‐NSs) as a universal precursor. We successfully synthesized the unprecedented AAS‐NSs in the hydrophilic space of the stable hyperswollen lyotropic lamellar (HL) phase. The four zeolite types could be obtained from the single‐species AAS‐NSs. These results imply that this method enables us to synthesize almost all types of zeolite‐NSs. Moreover, the synthesized CHA‐NSs have great potential for various applications because of their thickness and large external surface area. Abstract : A versatile method allows zeolite nanosheets (NSs) to be prepared from single‐species amorphous aluminosilicate NSs (AAS‐NSs). The AAS‐NSs were prepared by the two‐dimensional reactor in amphiphilic phases (TRAP) method. Using this approach four zeolite types were prepared from single‐species AAS‐NSs by the dry gel conversion (DGC) process with structure‐directing agents (SDAs).